HIGH-PRESSURE SYMPLECTITIC GARNET-CLINOPYROXENE-MARGARITE-MUSCOVITE-CLINOZOISITE AMPHIBOLITES OF THE DAKHOV BLOCK, NORTHERN CAUCASUS: GENESIS AND COMPOSITION OF REACTION TEXTURES - Korikovsky S.P.; Somin M.L.; Korsakov S.G. (My University, 2004)
The high-pressure character of the metamorphic rocks from the Dakhov Block makes them similar to the Blyb eclogite-bearing complex in the southern part of the Front Range, but the maximum pressures in the block were lower than in the Blyb Complex, at least in the part containing kyanite eclogites and showing evidence of pressures as high as 16 kbar. Other stratigraphic units of this complex also offer apparent evidence of high metamorphic pressures but no exact evaluations have been made for them as yet. The Dakhov and Blyb metamorphic rocks mark, along with the spatially related ultrabasites, a broad ancient (Late Paleozoic) subduction zone, the development of which may have induced many events during the pre-Alpine evolutionary stage of the Greater Caucasus.